The marking of two aspectual distinctions in Sign Language of the Netherlands (NGT) (Linguistics in Amsterdam, 2016)
This article reports on the results of a pilot study on aspect marking in Sign Language of the Netherlands (NGT). A deaf signer of NGT completed an adapted version of a questionnaire about tense, mood, and aspect marking in spoken languages (Dahl 1985). The resulting data provide the basis for a description of the manual and non-manual markers that signal continuative and habitual aspect in NGT. The results show that the main marker of the two aspectual distinctions is reduplication of the verb, accompanied by synchronous back-and-forth (continuative) and left-to-right (habitual) movements of the head and body. The findings challenge those reported in a similar study on aspectual marking by Hoiting &Slobin (2001) in two respects. Firstly, Hoiting and Slobin argue that elliptical modulation of a verb’s movement is a distinctive marker of continuative and habitual aspect, but no such modulation was attested in the data. Secondly, the authors claim that, in cases in which the phonological specifications of a verb block elliptical modulation, aspect is obligatorily marked sequentially by means of the aspectual particle DOOR (‘through’). However, since there was no elliptical modulation in the data, DOOR was also not attested. The results could point toward grammatical differences between different variants of NGT.